FROM THE PLAY DIE DREIGROSCHENOPER TO OPERA IKAN ASIN: A STUDY ON HANS ROBERT JAUSS’ HORIZON OF EXPECTATION - Isti Haryati (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This article aims to reveal how Riantiarno's horizon of expectation before reading the play Die Dreigroschenoper affects the results of his actualization in his play Opera Ikan Asin. The method that being used here is comparison and literature study method. The results show that not all of Riantiarno’s expectation were fullfiled. To fullfill the horizon of expectation, Riantiarno makes and adjustment. The unfulfillment in terms of theater norms have led to the inclusion of traditional elements into the play Opera Ikan Asin. Therefore, Brecht's play Die Dreigroschenoper gets Riantiarno closer to the tradition.